The Effect of Remuneration and Job Satisfaction on Teacher Performance with Organizational Citizenship Behavior (OCB) as Mediating Variable - Dina Ma'rifah; Iman Murtono Soenhadji (Dinamika Pendidikan, 2022)
The quality of education is one of the measurements in determining the quality of a nation because education can produce qualified human resources. The result of the PISA showed that the quality of education in Indonesia, from students’ literacy level, was in the low position because the quality of education was uneven, in this case, the performance of teachers. Teacher performance would affect the quality of students’ learning process. In addition, to create an effective organization, the attitude of teachers' professional performance needed to be supported by a voluntary attitude, namely Organizational Citizenship Behavior (OCB). This study aimed to analyze the direct and indirect effects of remuneration on teacher performance with OCB as mediation. This was associative research with the quantitative approach which aimed to find relations that explain measurable causes and facts, also show variable relations, and perform analysis. The subjects in this study were public and private high school teachers in Depok. The number of respondents was 250 teachers. A questionnaire was used as a data collection method. The analysis used was multiple linear regression and path analysis. Based on the results of the study, there was a joint influence between the variables of remuneration, job satisfaction, and OCB on teacher performance. The dominant variable that affected OCB and teacher performance was job satisfaction.